It's Not All About the Face: Variability Reveals Asymmetric Obligatory Processing of Faces and Bodies in Whole-Body Contexts. (June 2018) - Reed, Catherine L.; Bukach, Cindy M.; Garber, Matthew; McIntosh, Daniel N.
Researchers have sought to understand the specialized processing of faces and bodies in isolation, but recently they have considered how face and body information interact within the context of the whole body. Although studies suggest that face and body information can be integrated, it remains an open question whether this integration is obligatory and whether contributions of face and body information are symmetrical. In a selective attention task with whole-body stimuli, we focused attention on either the face or body and tested whether variation in the irrelevant part could be ignored. We manipulated orientation to determine the extent to which inversion disrupted obligatory face and body processing. Obligatory processing was evidenced as performance changes in discrimination that depended on stimulus orientation when the irrelevant region varied. For upright but not inverted face discrimination, participants could not ignore body posture variation, even when it was not diagnostic to the task. However, participants could ignore face variation for upright body posture discrimination but not for inverted posture discrimination. The extent to which face and body information necessarily influence each other in whole-body contexts appears to depend on both domain-general attentional and face- or body-specific holistic processing mechanisms.